2019
DOI: 10.1111/pbi.13089
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency Agrobacterium‐mediated site‐specific gene integration in maize utilizing the FLPFRT recombination system

Abstract: Summary An efficient Agrobacterium ‐mediated site‐specific integration ( SSI ) technology using the flipase/flipase recognition target ( FLP / FRT ) system in elite maize inbred lines is described. The system allows precise integration of a single copy of a donor DNA flanked by heterologous FRT sites into a predefined recombinant target line ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…Additionally, it is commonly accepted that recombinase coding sequences are degraded and eventually lost; however, Srivastava and Ow (2001) identified 40% of excision modifications contained a stably integrated Cre recombinase coding sequence after bombardment (Wang et al, 2011). Similarly, Anand et al (2019) reported the presence of FLP and/or Cre in T 0 plants when using Agrobacterium as the mode of delivery to induce a recombinase‐mediated cassette exchange reaction. Taken together, transient expression of recombinases using Agrobacterium or bombardment adds the benefit of timely modifications; however, it requires tissue culture and subsequent screening to obtain a desired plant background.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Additionally, it is commonly accepted that recombinase coding sequences are degraded and eventually lost; however, Srivastava and Ow (2001) identified 40% of excision modifications contained a stably integrated Cre recombinase coding sequence after bombardment (Wang et al, 2011). Similarly, Anand et al (2019) reported the presence of FLP and/or Cre in T 0 plants when using Agrobacterium as the mode of delivery to induce a recombinase‐mediated cassette exchange reaction. Taken together, transient expression of recombinases using Agrobacterium or bombardment adds the benefit of timely modifications; however, it requires tissue culture and subsequent screening to obtain a desired plant background.…”
Section: Discussionmentioning
confidence: 95%
“…The first application using Cre to excise a stably integrated selectable marker gene from tobacco occurred in the early 90s (Dale & Ow, 1990). Since then, recombinases have been used in a number of plant systems including rice (Hoa, Bong, Huq, & Hodges, 2002; Hu et al, 2007; Radhakrishnan and Srivastava, 2005), tobacco (Albert, Dale, Lee, & Ow, 1995; Dale & Ow, 1991), wheat (Srivastava, Anderson, & Ow, 1999), tomato (Stuurman, Vroomen, Nijkamp, & Haaren, 1996), barley (Kapusi, Kempe, Rubtsova, Kumlehn, & Gils, 2012), soybean (Li et al, 2009), Arabidopsis (Hong, Lyznik, Gidoni, & Hodges, 2000; Thomson, Chan, Thilmony, Yau, & Ow, 2010; Vergunst & Hooykaas, 1998), and maize (Anand et al, 2019; Kerbach, Lörz, & Becker, 2005; Lyznik, Rao, & Hodges, 1996; Srivastava & Ow, 2001; Zhang et al, 2003). In these studies, recombinase enzymes have been used for the purpose of selectable marker removal, transgene targeting to predetermined locations, or resolution of multiple transgene concatemers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each method has its own advantages and disadvantages. While recombinase-mediated methods are highly efficient in targeted integrations, e.g., with Cre-lox, FLP-FRT and other site-specific recombination systems, they require placement of recombination target sites that can subsequently be targeted for gene stacking (Anand et al, 2019;Li et al, 2009;Ow, 2003;Srivastava and Gidoni, 2010). The CRISPR/Cas9 method, on the other hand, can target virtually any site in the genome, but the non-homologous mode of DSB repair in plant cells overrides the integration of exogenous DNA into the DSB site (Puchta and Fauser, 2014;Voytas, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other site-specific recombination systems that show high efficiency in plant cells include FLP-FRT, phiC31-att and Bxb1-att systems (Anand et al, 2019;Hou et al, 2014;Li et al, 2009;Nandy et al, 2011;Ow, 2011;Thomson and Ow, 2006). Recombinase-mediated gene stacking has been demonstrated in soybean by inserting gene silencing and overexpression constructs through two rounds of transformation (Li et al, 2010).…”
Section: Introductionmentioning
confidence: 99%